Personality and online/offline choices: MBTI profiles and favored communication modes in a Singapore study - Goby, VP (Mary Ann Liebert Inc, 2006)
This study presents an initial investigation of the degree to which personality, as classified by the four dimensions of the Myers-Briggs Type Indicator (MBTI) affects an individual's choice of online or offline means for conducting social interactions. Results yield some evidence that personality affects choice of online or offline options, with an especially significant correlation between online/offline choices and the dimension of Extraversion and Introversion. Significant results are also seen for the Judging-Perception and Thinking-Feeling dimensions, but the Sensing-iNtuition dimension showed no correlation.
Keywords: Computer-Mediated Communication